HUBUNGAN ANTARA KEBIASAAN SARAPAN PAGI DENGAN KEBUGARAN JASMANI PADA SISWA SMA NEGERI 6 KOTA JAMBI - Amelia, Amelia; Decheline, Grafitte; Yudho Prabowo, Bangkit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe breakfast habits and physical fitness levels and to examine the relationship between breakfast habits and physical fitness among grade X students at SMA Negeri 6 Kota Jambi. The study used a quantitative correlational design. The respondents were 65 students from classes X3 and X6 who had complete questionnaire and Indonesian Physical Fitness Test (TKJI) data. Breakfast habits were measured using a Likert-scale questionnaire covering frequency, regularity, breakfast time, and nutritional fulfillment. Physical fitness was measured using the TKJI for the 16-19 year age group. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, and Spearman Rank correlation. The results showed that most students had good breakfast habits, with 31 students (47.69%) in the good category and 12 students (18.46%) in the very good category. The highest indicator score was breakfast frequency (mean per item = 3.74), while the lowest was breakfast regularity (mean per item = 3.51). Physical fitness was mostly in the moderate category, namely 27 students (41.54%), followed by the good category with 19 students (29.23%). The Spearman Rank test obtained a correlation coefficient of 0.547 with a significance value of <0.001. These findings indicate a positive and significant relationship of moderate strength between breakfast habits and physical fitness. Better breakfast habits tend to be followed by higher physical fitness levels, although the relationship should not be interpreted as direct causality.